The influence of stock markets on the formation of the value of Russian companies ("Journal "U". Economy. Management. Finance.", 2024)
The article presents the main factors of influence of stock markets on the formation of the value of Russian companies. In particular, the negative impact of ruble strengthening for exporting companies and the positive impact of ruble strengthening for importing companies are indicated; the change in the value of oil producing companies depending on changes in the oil price exchange rate is considered; the influence of world markets and anti-Russian sanctions policy is highlighted.
Keywords: stock market; share price; factors influencing the value of the company; the impact of the ruble exchange rate; the impact of oil prices; the impact of sanctions